Concept of Islamic Integrated Education and Its Implementation at Ar-Rohmah Educational Institute Malang - Rossidy, Imron; Ahmad Barizi; Abd Haris; Esa Nur Wahyuni (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2023)
The aim of this study reveals the concept of Islamic integrated education and its implementation at Ar-Rohmah Islamic boarding school Hidayatullah Malang. The method used in this study is qualitative, while data analysis uses qualitative descriptive analysis. The results of the data analysis show that integrated education at Ar-Rohmah has a solid foundation from the Al-Qur'an and Al-Hadith as well as the views of the Muslim scholars. The implementation of Islamic integrated education at this institution is manifested explicitly in the organization’s mission statement, namely to carry out tauhid-based integral education that combines tarbiyah ruhiyah (spiritual education), aqliyah (intellectual), and jismiyah (physical). This mission is a realization of Ar-Rohmah's vision, which is to create excellent and competitive educational institutions to produce a generation that is cautious, intelligent, and independent. The vision and mission are translated into the educational goals of Ar-Rohmah, which aims to shape humans according to the vision and mission of their creation, namely as a servant of Allah (‘abdullah) and His vicegerent (khalifah) with the following characteristics: first, to have a strong spiritual mentality- aspects of ruhiyah. Second, have the knowledge and breadth of insight into life -aspects of aqliyah. Third, have expertise and skills- aspects of jismiyah. This institution also implements an integrated curriculum through a combination of the national curriculum (K13), the religious curriculum (Diniyah Khas), and the Hidayatullah Specific Parenting Curriculum (Kurikulum Kepengasuhan Khas). As well as integrated between formal schools and religious schools (madrasah diniyah).